Structural properties and in vitro digestibility of edible and pH-sensitive films made from guinea arrowroot starch and wastes from wine manufacture - Gutiérrez Carmona, Tomy José (2018)
A non-conventional starch obtained from guinea arrowroot tubers (Calathea allouia) grown in the Amazon was used as a polymeric matrix for the development of edible films. The films were manufactured by blending/thermo molding and plasticized with glycerol. Agro-industrial wastes from wine manufacture (grape waste flour and grape waste extract) were used as natural fillers of the thermoplastic starch (TPS) matrices. The results showed that the natural fillers caused cross-linking in the TPS matrix. This led to the production of films with higher resistant starch (RS) content, especially RS type 4 (RS4), although the DSC results showed that the films developed also contained RS type 3 (RS3). As expected, the presence of RS reduced the in vitro digestibility rate. Films made with the natural fillers were also less hydrophilic, had a greater thermal resistance, and tended towards ductile mechanical behavior. Finally, the edible film containing grape waste flour as a natural filler proved to be pH-sensitive, although this material disintegrated under alkaline conditions.